Rain-Grove a stand-alone rainwater harvesting system designed for Ninoy Aquino Parks and Wildlife, Quezon City - Velarde, Gillian Pamela V.
The interconnected systems of parks and green spaces that conserves natural ecosystem values and sustains clear air and water are a community necessity. According to the Environmental Science for Social Change, by this year the Philippines will experience drought with or without El Niño. The demand for water will escalate to a point that water allocation to parks will most likely be reduced in order to give way to households in need. Rain water is a vastly underused resource that we often take for granted. Rain water harvesting is an old-age concept that is increasing popularity today. With this, I designed a stand-alone rain water harvesting system for Ninoy Aquino Parks and Wildlife Center. Aside from it being a water utility system, it is also designed to function as a park attraction. This is also a perfect practice to responsible water management. Climate change is real.